The Advanced Organ Support (ADVOS) hemodialysis system fulfills its intended purpose: Analysis of data from 282 patients from the Registry on Extracorporeal Multiple Organ Support (EMOS) - Valentin Fuhrmann; Bartosz Tyczynski; Aritz Perez Ruiz de Garibay; Tobias Michael Bingold; Julia Weinmann-Menke; Andreas Faltlhauser; Dominik Jarczak; Jens Lutz; Michael Sander; Pascal Klimpke; Christian Koch; Andreas Kribben; et al. (PLoS ONE, 2025)
Several case series have highlighted the ADVOS hemodialysis system’s efficacy in eliminating water-soluble and protein-bound substances across diverse patient populations, such as multiorgan failure, acute-on-chronic liver failure (ACLF), acidosis, and even COVID-19. The EMOS-Registry, a non-interventional, multi-center patient registry, amassed real-world evidence, culminating in the largest patient cohort treated with ADVOS to date. This study aims to present and analyze the final performance and safety outcomes from the entire dataset comprising 282 participants. Data spanning from January 18, 2017, to August 31, 2020, were collected from five German hospitals, encompassing subsets of patients with acidosis and ACLF grade 3. Performance and safety were assessed through vital signs, clinical laboratory parameters and blood gas analyses. The SOFA Score-Standardized Mortality Ratio (SMR) served to evaluate patient outcomes in the absence of a control group. Participants, with a median age of 58 years, predominantly male (64%), exhibited a high requirement for mechanical ventilation (68%) and vasopressors (82%) with a median SOFA Score of 15. Notably, a median of 3 (IQR 2, 5) ADVOS sessions per patient were administered. Following the initial treatment, significant reductions were observed in bilirubin (−1.9 [CI 95% −1.3, −2.5]), creatinine (−0.5 [−0.4, −0.6]), and blood urea nitrogen (−13.1 mg/dL [−10.3, −16.0]) levels. Moreover, there were marked improvements in blood pH (7.34 vs. 7.41, p < 0.001), HCO 3 - (19.4 vs. 24.6 mmol/l, p < 0.001) and base excess (−5.6 vs. 0.2 mmol/l, p < 0.001). The observed mortality rate (66%) was notably lower than the expected rate based on SOFA Score (84%), resulting in a SMR of 0.79 (95% CI: 0.66–0.93), with a calculated number needed to treat (NNT) of 5.8. This study emphasizes the ADVOS system’s efficacy in eliminating water-soluble and protein-bound substances and correcting acid-base imbalances across a diverse cohort with multiorgan failure. However, further validation through randomized controlled trials is warranted to solidify these findings. Trial registration DRKS00017068. Registered 29 April 2019 – Retrospectively registered, https://drks.de/search/en/trial/DRKS00017068